Isolation of Bordetella avium and Novel Bordetella Strain from Patients with Respiratory Disease - Amanda T. Harrington; Jaime A. Castellanos; Tomasz M. Ziedalski; Jill E. Clarridge; Brad T. Cookson (Emerging Infectious Diseases, 2009)
Bordetella avium is thought to be strictly an avian pathogen. However, 16S rRNA gene sequencing identified 2 isolates from 2 humans with respiratory disease as B. avium and a novel B. avium–like strain. Thus, B. avium and B. avium–like organisms are rare opportunistic human pathogens.